Advances in through-life engineering services - Redding, Louis; Roy, R. 1966-; Shaw, Andy, 1956- (Decision engineering, 2017)
This edited book offers further advances, new perspectives, and developments from world leaders in the field of through-life engineering services (TES). It builds up on the earlier book by the same authors entitled: "Through-life Engineering Services: Motivation, Theory and Practice." This compendium introduces and discusses further, the developments in workshop-based and 'in situ' maintenance and support of high-value engineering products, as well as the application of drone technology for autonomous and self-healing product support. The links between 'integrated planning' and planned obsolescence, risk and cost modelling are also examined. The role of data, information, and knowledge management relative to component and system degradation and failure is also presented. This is supported by consideration of the effects upon the maintenance and support decision by the presence of 'No Fault Found' error signals within system data. Further to this the role of diagnostics and prognostics is also discussed. In addition, this text presents the fundamental information required to deliver an effective TES solution/strategy and identification of core technologies. The book contains reference and discussion relative to automotive. rail, and several other industrial case studies to highlight the potential of TES to redefine the product creation and development process. Additionally the role of warranty and service data in the product creation and delivery system is also introduced. This book offers a valuable reference resource for academics, practitioners and students of TES and the associated supporting technologies and business models that underpin whole-life product creation and delivery systems through the harvesting and application of condition and use based data.